The Influence of Work Training, Physical Work Environment, and Work Discipline, on The Performance of Employees of The Republic of Indonesia Ombudsman - Maniihuruk, Cindy Widya; Krisnandi, Herry; Digdowiseiso, Kumba (Ridwan Institute, 2024)
This study aims to determine and analyze the effect of Job Training, Physical Work Environment, and Work Discipline on the Performance of Employees at the Central Indonesian Ombudsman Institute. The research data uses primary data in questionnaires to 100 respondents to the central RI Ombudsman. The data analysis method uses inferential analysis with multiple linear regression and uses the Statistical Product and Service Solution (SPSS) version 26.0 program. The results of multiple linear regression analysis show that the variables Job Training (X1), Physical Work Environment (X2), and Work Discipline (X3) have a positive and significant effect on Employee Performance (Y). The results of this study show that the Indonesian Ombudsman can pay attention to Job Training, Physical Work Environment, and Work Discipline to improve Employee Performance.